PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DEPARTEMEN SEWING (LINE A-W) PADA PT. SANDANG ASIA MAJU ABADI - Diyah Sari Ika; Agus Hermani DS (Universitas Diponegoro, 2019)
PT. Sandang Asia Maju Abadi is a garment company that manufactures superior denim products for men and women of all age groups. This study aims to determine the effect of work discipline and work motivation on the sewing performance of the sewing department (Line A-W) at PT. Sandang Asia Maju Abadi. The type of research used is explanatory research. The sample used was 89 respondents in the sewing department employee (Line A-W) at PT. Sandang Asia Maju Abadi. Data collection uses a questionnaire with a Likert measurement scale. The results showed that partially the work discipline variables and work motivation had an effect on employee performance positively and significantly with regression coefficient values on the variables of work discipline (0.855) and work motivation (0.649) and the value of work discipline variables (5.829) and motivation work (4,869). And simultaneously the work discipline and work motivation variables jointly influence the employee performance variables positively and significantly with the multiple regression coefficient of the work discipline variable (0.644) and work motivation (0.377) with the calculated value (21.740).